Electrode composition for lithium ion battery and method for manufacturing electrode for lithium ion battery

JP2025030745APending Publication Date: 2025-03-07SANYO CHEM IND LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023136306
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、電極の柔軟性が高く、かつ充放電効率(クーロン効率)及びサイクル特性に優れた電極を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030745000001
    Figure 2025030745000001
  • Figure 2025030745000002
    Figure 2025030745000002
  • Figure 2025030745000003
    Figure 2025030745000003
Patent Text Reader

Abstract

To provide an electrode composition capable of producing an electrode having high mechanical strength and flexibility, and excellent charge / discharge efficiency (Coulombic efficiency) and cycle characteristics.SOLUTION: An electrode composition for a lithium ion battery, includes a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material, and the weight ratio of a monomer contained in the electrode composition is 1,000 to 20,000 ppm on the basis of the weight of the electrode composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode composition for a lithium ion battery and a method for producing an electrode for a lithium ion battery. [Background technology]

[0002] Lithium-ion batteries, which have the characteristics of high voltage and high energy density, are widely used in the field of portable information devices, and have established their position as the standard battery for portable terminals such as mobile phones and notebook computers. As their uses expand, their application to hybrid and electric vehicles, in addition to the conventional applications, is being considered, and some have already been put into practical use. In order to further popularize these, there is a demand for lithium-ion batteries with higher capacity and power output, and various technologies are being attempted to apply them.

[0003] One method for improving the capacity of secondary batteries is to increase the electrode density. By reducing the content of binders, conductive fillers, dispersants, etc. and packing more active materials densely, a larger capacity can be obtained. However, reducing the content of binders, conductive fillers, dispersants, etc. can lead to problems such as a decrease in the strength (especially flexibility) of the electrodes and a deterioration in battery performance.

[0004] In order to solve such problems, Patent Document 1 discloses a method for manufacturing a lithium-ion battery in which a dried active material and a dried binder are mixed and dry-molded to uniformly disperse the active material substantially free of processing additives such as solvents and residues generated from the solvent. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2021-504877 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the method of Patent Document 1, the resulting electrode thin film is a self-forming thin film formed from a dry particle mixture, and therefore the electrode tends to lack flexibility. This tendency is particularly noticeable when attempting to thicken the electrode film to improve the capacity of lithium-ion batteries.

[0007] The present invention is devised to solve the above-mentioned problems, and has an object to provide an electrode composition for lithium ion batteries and a method for producing a lithium ion electrode, which are capable of producing an electrode having high flexibility and excellent charge / discharge efficiency (Coulombic efficiency) and cycle characteristics. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors arrived at the present invention. The present invention relates to an electrode composition for lithium ion batteries, which contains a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material, wherein the weight ratio of a monomer contained in the electrode composition to be subjected to the forming step is 1,000 to 20,000 ppm based on the weight of the electrode composition; and a method for producing an electrode for lithium ion batteries. Effect of the Invention

[0009] According to the present invention, it is possible to provide an electrode which is highly flexible and has excellent charge / discharge efficiency (Coulombic efficiency) and cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention is an electrode composition for lithium ion batteries, which contains a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material. In this specification, (meth)acrylic acid means acrylic acid and / or methacrylic acid, and (co)polymer means a copolymer or a polymer.

[0011] The (meth)acrylic acid (co)polymer may be a copolymer of acrylic acid and / or methacrylic acid with other monomers, such as methyl acrylate, methyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 1,6-hexanediol diacrylate, and styrene. From the viewpoint of electrode strength etc., the ratio of the total weight of acrylic acid and methacrylic acid to the total weight of acrylic acid, methacrylic acid and other monomers is preferably 25 to 90% by weight, more preferably 55 to 90% by weight.

[0012] The (meth)acrylic acid (co)polymer may be one obtained by polymerizing the above-mentioned monomers by a known method, or a commercially available (meth)acrylic acid (co)polymer may be used. As commercially available (meth)acrylic acid (co)polymers, polyacrylic acid manufactured by Toagosei Co., Ltd. and reagents manufactured by Wako Pure Chemical Industries, Ltd. can be used. As the (meth)acrylic acid (co)polymer that can be used, not only those sold as binders but also those sold as dispersants can be used in the same way.

[0013] The (meth)acrylic acid (co)polymer preferably has a glass transition temperature of −25 to 100° C. When the (meth)acrylic acid (co)polymer has a glass transition temperature within this range, the mechanical strength of the resulting electrode is improved. The glass transition temperature of the (meth)acrylic acid (co)polymer is measured in accordance with JIS K 6240:2011 Raw rubber - Determination of glass transition temperature by differential scanning calorimetry (DSC).

[0014] The weight average molecular weight of the (meth)acrylic acid (co)polymer is preferably 50,000 to 200,000, and more preferably 80,000 to 150,000, from the viewpoint of achieving both strength and handleability of the resulting electrode.

[0015] The weight average molecular weight of the (meth)acrylic acid (co)polymer can be determined by gel permeation chromatography (hereinafter abbreviated as GPC) measurement under the following conditions. Apparatus: Alliance GPC V2000 (Waters) Solvent: orthodichlorobenzene, DMF, THF Standard material: polystyrene Sample concentration: 3mg / ml Column stationary phase: PLgel 10 μm, MIXED-B 2 columns in series (Polymer Laboratories) Column temperature: 135℃

[0016] Examples of the conductive carbon filler include graphite, carbon black (acetylene black, ketjen black, furnace black, channel black, thermal lamp black, etc.), and mixtures thereof. Note that the conductive carbon filler is not necessarily limited to these.

[0017] The electrode active material may be a positive electrode active material for a lithium ion battery (also simply referred to as a positive electrode active material) or a negative electrode active material for a lithium ion battery (also simply referred to as a negative electrode active material).

[0018] The positive electrode active material may be a composite oxide of lithium and a transition metal {composite oxides containing one type of transition metal element (e.g., LiCoO2, LiNiO2, LiAlMnO4, LiMnO2, and LiMn2O4), composite oxides containing two types of transition metal elements (e.g., LiFeMnO4, LiNi 1-x Co x O2, LiMn 1-y Co y O2, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O2 and LiNi 0.8 Co 0.15 Al 0.05 O2) and composite oxides containing three or more transition metal elements [e.g. LiM a M' b M'' cO2(M, M' and M'' are different transition metal elements and satisfy a+b+c=1. For example, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 Examples of the conductive polymer include lithium-containing transition metal phosphates (e.g., LiFePO4, LiCoPO4, LiMnPO4, and LiNiPO4), transition metal oxides (e.g., MnO2 and V2O5), transition metal sulfides (e.g., MoS2 and TiS2), and conductive polymers (e.g., polyaniline, polypyrrole, polythiophene, polyacetylene, poly-p-phenylene, and polyvinylcarbazole), and two or more of these may be used in combination. The lithium-containing transition metal phosphate may have some of the transition metal sites substituted with other transition metals.

[0019] From the viewpoint of the electrical characteristics of the battery, the positive electrode active material preferably has a volume average particle size of 0.01 to 100 μm, more preferably 0.1 to 35 μm, and even more preferably 2 to 30 μm. In this specification, the volume average particle size refers to the particle size (Dv50) at an integrated value of 50% in the particle size distribution determined by the Microtrack method (laser diffraction / scattering method). The Microtrack method is a method for determining the particle size distribution by utilizing scattered light obtained by irradiating particles with laser light. The volume average particle size can be measured using a Microtrack manufactured by Nikkiso Co., Ltd.

[0020] Examples of the negative electrode active material include carbon-based materials [graphite, non-graphitizable carbon (hard carbon), amorphous carbon, resin baked bodies (e.g., phenolic resins and furan resins baked and carbonized, etc.), cokes (e.g., pitch coke, needle coke, and petroleum coke, etc.), and carbon fibers, etc.], silicon-based materials [silicon, silicon oxide (SiO x), silicon-carbon composites (carbon particles whose surfaces are coated with silicon and / or silicon carbide, silicon particles or silicon oxide particles whose surfaces are coated with carbon and / or silicon carbide, and silicon carbide, etc.) and silicon alloys (silicon-aluminum alloy, silicon-lithium alloy, silicon-nickel alloy, silicon-iron alloy, silicon-titanium alloy, silicon-manganese alloy, silicon-copper alloy, silicon-tin alloy, etc.), conductive polymers (e.g. polyacetylene, polypyrrole, etc.), metals (tin, aluminum, zirconium, titanium, etc.), metal oxides (titanium oxide, lithium-titanium oxide, etc.) and metal alloys (e.g. lithium-tin alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.), and mixtures of these with carbon-based materials.

[0021] From the viewpoint of increasing the electric capacity, the negative electrode active material is preferably non-graphitizable carbon or a mixture of non-graphitizable carbon and a silicon-based material.

[0022] From the viewpoint of the electrical characteristics of the battery, the negative electrode active material preferably has a volume average particle size of 0.01 to 100 μm, more preferably 0.1 to 60 μm, and even more preferably 2 to 40 μm.

[0023] The present invention is an electrode composition for lithium ion batteries, which contains a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material. In the electrode composition, the weight ratio of the (meth)acrylic acid (co)polymer is preferably 0.5 to 10% by weight based on the weight of the electrode composition. When the weight ratio of the (meth)acrylic acid (co)polymer is in this range, the mechanical strength of the obtained electrode is improved. In the electrode composition, the weight ratio of the conductive carbon filler is preferably 0.5 to 10% by weight based on the weight of the electrode composition. When the weight ratio of the conductive carbon filler is in this range, the performance (cycle characteristics) of the obtained battery is improved. In the electrode composition, the weight ratio of the electrode active material is preferably 78 to 99% by weight based on the weight of the electrode composition. When the weight ratio of the electrode active material is in this range, the performance (coulombic efficiency) of the obtained battery is improved.

[0024] The lithium ion battery electrode composition of the present invention includes a monomer. The weight ratio of the monomer contained in the electrode composition to be subjected to the forming step is 1,000 to 20,000 ppm based on the weight of the electrode composition. If the weight ratio of the monomer contained in the electrode composition is less than 1,000 ppm based on the weight of the electrode composition when subjected to the forming step, the mechanical strength of the obtained electrode is reduced, and if the weight ratio of the monomer contained in the electrode composition is more than 20,000 ppm based on the weight of the electrode composition, the battery characteristics (cycle characteristics) are deteriorated.

[0025] As the monomer contained in the electrode composition, the monomers exemplified as the monomers used in polymerizing the above-mentioned (meth)acrylic acid (co)polymer can be suitably used. The monomer contained in the electrode composition may be a monomer (residual monomer) that remains unreacted during synthesis of the (meth)acrylic acid (co)polymer, or may be a monomer that is separately added to the electrode composition.

[0026] The monomer contained in the electrode composition can be adjusted by controlling the polymerization conditions of the (meth)acrylic acid (co)polymer, adding it separately to the electrode composition, etc. Specifically, the reaction rate can be decreased by decreasing the polymerization temperature of the (meth)acrylic acid (co)polymer, and the weight ratio of the remaining monomer can be increased.

[0027] From the viewpoint of ease of formation of an insulating coating on an electrode active material, the monomer contained in the electrode composition is preferably one or more selected from the group consisting of acrylic acid, methacrylic acid, methyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, and 1,6-hexanediol diacrylate.

[0028] The weight ratio of the monomer contained in the electrode composition can be measured, for example, by the following method. First, the lithium ion battery electrode composition is placed in a screw tube and immersed in deuterated chloroform to extract the monomer. The chloroform extract is mixed with an internal standard of known purity (e.g., γ-butyrolactone) to form mixture A. 1 Measured by H-NMR. Separately, a mixture of monomer standards of known purity and an internal standard (e.g., γ-butyrolactone) was also prepared. 1 Measured by H-NMR. Monomer standard sample and chloroform extract 1 The weight can be calculated from the integral ratio of the monomer peak in the H-NMR chart. The mixture ratio of the chloroform extract and the internal standard in mixed solution A is prepared to be the same as the mixture ratio of the monomer standard sample and the internal standard in mixed solution B.

[0029] The weight proportion of the monomer contained in the lithium ion battery electrode after molding the lithium ion battery electrode composition by the method described below can be measured by changing the lithium ion battery electrode composition in the measurement method for the weight proportion of the monomer contained in the lithium ion battery electrode composition to the molded electrode.

[0030] In the electrode composition for lithium ion batteries of the present invention, the ratio of the weight proportion of the monomer to the weight proportion of the conductive carbon filler (weight proportion of monomer / weight proportion of conductive carbon filler) is preferably 4 to 60%, and more preferably 20 to 45%. When the ratio of the weight proportion of the monomer to the weight proportion of the conductive carbon filler is within the above range, the dispersibility of the conductive carbon filler is improved, and the performance of the resulting battery is improved.

[0031] The method for producing an electrode for a lithium ion battery of the present invention includes a molding step of molding the electrode composition. The forming of the electrode composition may be a dry forming process in which the (meth)acrylic acid (co)polymer, the conductive carbon filler, the electrode active material, etc. are mixed (dry blended) in a dry state and compressed to form, or a wet forming process in which the electrode composition further containing a solvent, etc. is compressed and molded, and then integrated through a drying process. From the viewpoints of uniformity of the obtained electrode and ease of forming, the dry forming process is preferred.

[0032] As the mixer used in the dry process, a known powder mixer can be used, and any of a container rotation type mixer, a fixed container type mixer, and a fluid motion type mixer can be used. For example, as a fixed container type mixer, a method of dry blending using a high-speed fluid type mixer, a double-shaft paddle type mixer, a high-speed shear mixer (Henschel mixer, etc.), a low-speed mixer (planetary mixer), and a conical screw mixer (Nauter Mixer (registered trademark)) is well known. Among these methods, it is preferable to use a double-shaft paddle type mixer, a low-speed mixer (planetary mixer), and a conical screw mixer (Nauter Mixer (registered trademark)).

[0033] The present specification describes the following inventions: [1] An electrode composition for a lithium ion battery comprising a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material, An electrode composition for a lithium ion battery, wherein the weight ratio of the monomer contained in the electrode composition is 1,000 to 20,000 ppm based on the weight of the electrode composition. [2] The electrode composition for lithium ion batteries according to the above [1], wherein the monomer is at least one selected from the group consisting of acrylic acid, methacrylic acid, methyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate and 1,6-hexanediol diacrylate. [3] The electrode composition for lithium ion batteries according to the above [1] or [2], wherein the (meth)acrylic acid (co)polymer has a glass transition temperature of -25 to 100°C. [4] The weight ratio of the (meth)acrylic acid (co)polymer in the electrode composition is 0.5 to 10% by weight based on the weight of the electrode composition; the weight ratio of the conductive carbon filler in the electrode composition is 0.5 to 10% by weight based on the weight of the electrode composition; The electrode composition for lithium ion batteries according to any one of the above [1] to [3], wherein the weight ratio of the electrode active material in the electrode composition is 78 to 99% by weight based on the weight of the electrode composition. [5] A method for producing an electrode for a lithium ion battery by forming an electrode composition containing a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material, the method comprising the step of forming the electrode composition, A method for producing an electrode for a lithium ion battery, wherein the weight ratio of the monomer contained in the electrode composition provided to the forming step is 1,000 to 20,000 ppm based on the weight of the electrode composition. EXAMPLES

[0034] The present invention will now be described in detail with reference to examples. However, the present invention is not limited to these examples as long as it does not depart from the gist of the present invention.

[0035] (Production Example 1: Production of (meth)acrylic acid (co)polymer (A-1)) 27 parts by weight of methacrylic acid, 68 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of styrene, and 70 parts by weight of toluene were charged into a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen gas inlet tube, and the temperature was raised to 65°C. Furthermore, 10 parts by weight of toluene and 0.200 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) were mixed. The obtained monomer mixture was continuously dropped into the flask over 4 hours using a dropping funnel while blowing nitrogen into the flask, to carry out radical polymerization. The temperature was raised to 75°C, polymerization was continued for 2 hours, and toluene was added to obtain a (meth)acrylic acid (co)polymer (A-1) solution with a resin concentration of 25% by weight. The monomer content in the (meth)acrylic acid (co)polymer (A-1) solution is1 It was determined by 1 H-NMR to be 3% by weight.

[0036] (Production Examples 2 to 6: Production of (meth)acrylic acid (co)polymers (A-2) to (A-6)) As shown in Table 1, (meth)acrylic acid (co)polymer (A-2) to (A-6) solutions having a resin concentration of 25% by weight according to Production Examples 2 to 6 were prepared in the same manner as Production Example 1, except that the various constituents, weight ratios, and reaction solvents were changed.

[0037] [Table 1]

[0038] Example 1 Cathode active material particles (LiNi 0.8 Co 0.15 Al 0.05 90 parts by weight of O2 powder, manufactured by Toda Kogyo Co., Ltd., indicated as NCA), 5 parts by weight of acetylene black (AB) [DENKA BLACK Li-100, manufactured by Denka Co., Ltd.], and 20 parts by weight (solid content: 5 parts by weight) of the (meth)acrylic acid (co)polymer (A-1) solution (25% by weight solution) were charged, and 0.49 parts by weight of methacrylic acid as an additional monomer and 85 parts by weight of toluene as an additional solvent were added, followed by stirring with a mixer at 2000 rpm for 1 minute to prepare an electrode composition for a lithium ion battery. This electrode composition was applied to an aluminum foil having a thickness of 20 μm with an applicator so that the film thickness after drying would be 100 μm, and then dried at 100° C. for 2 hours to obtain an electrode sheet.

[0039] (Examples 2 to 10 and Comparative Examples 1 to 5) As shown in Table 2, a lithium ion battery electrode composition and an electrode sheet were produced in the same manner as in Production Example 1, except that the various constituent types and weight ratios were changed.

[0040] [Table 2]

[0041] Example 11 Into a 100 L Nauta mixer, 90 parts by weight of graphite particles, 5 parts by weight of acetylene black (AB) [DENKA BLACK Li-100, Denka Co., Ltd.], and 20 parts by weight (solid content: 5 parts by weight) of the (meth)acrylic acid (co)polymer (A-3) solution (25% by weight solution) were placed, and 1.41 parts by weight of methacrylic acid was further added, followed by mixing at 100° C. for 3 hours to prepare an electrode composition for a lithium ion battery. The obtained electrode composition for lithium ion batteries was fed through a hopper into a powder feeder equipped with a shaking device, and an electrode sheet was produced using a powder rolling machine "PRM-63D" (manufactured by Ohno Roll Co., Ltd.) The thickness of the electrode sheet was adjusted to 100 μm.

[0042] (Examples 12 and 13 and Comparative Example 6) As shown in Table 3, a lithium ion battery electrode composition and an electrode sheet were produced in the same manner as in Production Example 11, except that the various constituent types and weight ratios were changed.

[0043] [Table 3]

[0044] Details of the abbreviations listed in Tables 2 and 3 are as follows: NCA:LiNi 0.8 Co 0.15 Al 0.05 O2 powder [made by Toda Kogyo] Gr: Graphite particles "SNG-WXA1" [JFE Chemical Corporation] AB: Acetylene black "DENKA BLACK Li-100" [manufactured by Denka Co., Ltd.] KB: Ketjen Black "Ketjen Black EC300J" [Manufactured by Lion Specialty Chemicals Co., Ltd.] CNT: Carbon nanotube "NC7000" [Nanocyl]

[0045] <Grid test> The electrode compositions obtained in Examples 1 to 10 and Comparative Examples 1 to 5 were subjected to a cross-cut test. The cross-cut test was performed by the following method. The electrode composition was applied to an aluminum plate having a thickness of 0.5 mm with an applicator so that the film thickness after drying would be 180 μm, and then dried at 100° C. for 2 hours to obtain an electrode sheet. This electrode sheet was measured in accordance with JIS K5400-5-6. The results are shown in Table 2. [Evaluation Criteria] ◎: No peeling at all ○: Peeling is less than 10% △: Peeling is 10% or more but less than 30% ×: Peeling is 30% or more

[0046] <Bending Test> The bending test indicates the flexibility of the electrode, and was observed by the following method. For Examples 1 to 10 and Comparative Examples 1 to 5, the obtained electrode composition was applied to aluminum foil having a thickness of 20 μm with an applicator so that the film thickness after drying would be 180 μm, and then dried at 100° C. for 2 hours to obtain an electrode sheet. For Examples 11 to 13 and Comparative Example 6, the obtained lithium ion battery electrode composition was fed through a hopper into a powder feeder equipped with a shaking device, and an electrode sheet was produced using a powder rolling machine "PRM-63D" (manufactured by Ohno Roll Co., Ltd.) The thickness of the electrode sheet was adjusted to 100 μm. The obtained electrode sheet was wrapped around a rod of a given Φ (mm) with both ends fixed, and a weight of 100 g was hung from the electrode sheet. The size of Φ (mm) was gradually reduced, and the Φ (mm) at which the electrode began to crack was observed. The results are shown in Tables 2 and 3. Note that the electrode sheet obtained in Comparative Example 6 could not be measured because it cracked when it was wrapped around the rod.

[0047] <Surface resistance measurement> The electrode sheets obtained in Examples 1 to 13 and Comparative Examples 1 to 6 were each cut into strips measuring 3 cm x 10 cm to prepare measurement samples. The surface resistance was measured using a low resistivity meter [MCP-T610, manufactured by Mitsubishi Chemical Analytech Co., Ltd.] using the four-probe method in accordance with JIS K7194, and the electrical resistance value (Ω / □) of the electrode sheet surface was determined.

[0048] (Preparation of electrolyte) An electrolyte solution was prepared by dissolving LiPF6 at a ratio of 1 mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of EC:DEC = 1:1.

[0049] (Examples 21 to 28 and Comparative Examples 21 to 25: Preparation of Evaluation Batteries) The electrode sheets obtained in Examples 1, 2, 6 to 8, 11, and 13 and Comparative Examples 2 to 4 were punched out to a diameter of Φ15 mm to prepare positive electrodes for lithium ion batteries. Moreover, the electrode sheets obtained in Examples 3 to 5, 9, 10, and 12 and Comparative Examples 1, 5, and 6 were punched out to a diameter of Φ16 mm to prepare negative electrodes for lithium ion batteries. The lithium ion battery positive electrodes were placed at both ends of a 2032 coin cell together with the lithium ion battery negative electrodes according to the combinations listed in Table 4. As the current collector on the positive electrode side, an aluminum foil having a thickness of 20 μm was used. A separator (Celgard 3501) was inserted between the electrodes to create a battery cell for evaluation. The above electrolyte was poured into a battery cell for evaluation and sealed to prepare a battery for evaluation.

[0050] <Initial Coulombic Efficiency Measurement> The prepared evaluation battery was used to evaluate the initial performance of the lithium ion battery at 25° C. using a charge / discharge measuring device "HJ-SD8" [manufactured by Hokuto Denko Corporation] according to the following method. Using a constant current constant voltage charging method (also known as CCCV mode), the battery was charged to 4.2 V at a current of 0.05 C, and then charged while maintaining 4.2 V until the current value dropped to 5% of the initial current value. After a 10-minute break, the battery was discharged to 1.5 V at a current of 0.05 C. The charged capacity at this time was defined as [initial charge capacity (mAh)], and the discharged capacity was defined as [initial discharge capacity (mAh)]. Using the initial charge capacity and initial discharge capacity obtained in the above measurements, the initial coulombic efficiency was calculated according to the following formula. The results are shown in Table 4. [Initial coulombic efficiency (%)] = [Initial discharge capacity] ÷ [Initial charge capacity] × 100

[0051] <Measurement of cycle characteristics> A charge / discharge test was carried out using the prepared evaluation battery at 45° C. using a charge / discharge measuring device “HJ-SD8” [manufactured by Hokuto Denko Corporation] according to the following method. The battery was charged to 4.2V using a constant current / constant voltage method (0.05C), then after a 10-minute rest, it was discharged to 2.6V using a constant current method (0.05C). This cycle was repeated 20 times, and the ratio of the discharge capacity obtained in each cycle between the 1st and 20th cycles (100 × 20th discharge capacity / 1st discharge capacity) was taken as the cycle characteristic (%). The results are shown in Table 4.

[0052] [Table 4] [Industrial Applicability]

[0053] Lithium ion batteries equipped with electrodes obtained from the lithium ion battery electrode composition of the present invention are used particularly for stationary power sources, mobile phones, personal computers, hybrid cars, electric cars, and the like.

Claims

1. An electrode composition for a lithium ion battery comprising a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material, The weight ratio of the monomer contained in the electrode composition is 1,000 to 20,000 ppm based on the weight of the electrode composition.

2. The electrode composition for lithium ion batteries according to claim 1, wherein the monomer is at least one selected from the group consisting of acrylic acid, methacrylic acid, methyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, and 1,6-hexanediol diacrylate.

3. The electrode composition for lithium ion batteries according to claim 1, wherein the (meth)acrylic acid (co)polymer has a glass transition temperature of -25 to 100°C.

4. the weight ratio of the (meth)acrylic acid (co)polymer in the electrode composition is 0.5 to 10% by weight based on the weight of the electrode composition; the weight ratio of the conductive carbon filler in the electrode composition is 0.5 to 10% by weight based on the weight of the electrode composition; 2. The electrode composition for lithium ion batteries according to claim 1, wherein the weight ratio of the electrode active material in the electrode composition is 78 to 99% by weight based on the weight of the electrode composition.

5. A method for producing an electrode for a lithium ion battery, comprising forming an electrode composition containing a (meth)acrylic acid (co)polymer, a conductive carbon filler, and an electrode active material, the method comprising the steps of: forming the electrode composition; a weight ratio of the monomer contained in the electrode composition provided to the forming step is 1,000 to 20,000 ppm based on the weight of the electrode composition.

Citation Information

Patent Citations

  • Compositions and methods for energy storage devices with improved performance

    JP2021504877A